INOVASI LAYANAN PERPUSTAKAAN SELAMA PANDEMI COVID-19 OLEH TAMAN BACA MASYARAKAT OMAH BUKU DI DESA BLONDO KABUPATEN MAGELANG - Rasyid Jauhari; Sukaesih Sukaesih; Evi Nursabti Rukmana; Samson CMS (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2021)
This research discusses Library Service Innovations during the Covid-19 Pandemic by the Omah Buku Community Reading Park in Blondo Village, Magelang Regency. The purpose of this study was to determine the condition of library services in the Omah Buku Reading Park before and during the Covid-19 pandemic and the innovations made in dealing with it. This research is a research that uses a descriptive qualitative research method, where data collection is carried out by means of observation and interviews. Interviews were conducted with two participants, namely between the researcher and the owner and chairman of the Omah Buku Community Reading Park. The data that has been obtained from observation and interview activities are then processed and analyzed using data analysis techniques by exploring real life, contemporary limited systems or cases or various limited systems or various cases, with detailed and in-depth data collection techniques involving multiple sources of information. as well as reporting case descriptions and research case themes to help facilitate the process of interpretation of how innovative activities during the Covid-19 pandemic at TBM Omah Buku are interpreted and linked to existing theories. Based on the data that has been collected and processed, this study shows that there is a significant difference in service aspects between the time before and during the Covid-19 pandemic. The difference in this aspect of service then becomes the cause of the emergence of innovation and actions such as running activities while adhering to health protocols, limiting the number of visitors, delivery of library material collections by volunteers to several points in the surrounding community. This innovation is expected to attract people's attitudes to pay attention to the importance of reading gardens in the community.